Analysis and evaluation of economic models of use and development of digital space on the example of the Eurasian Economic Union (EAEU) (Journal of Economic Research & Business Administration, 2019)
This article discusses and analyzes the features of the application of economic models of digitalization of the countries of the Eurasian Economic Union. The current state of economies cannot be imagined without information technology and digital space. Especially this influence is felt with the advent of the Internet, mobile communications, social networks, which are constantly updated with new tools. The CIS countries are united not only geopolitically, but also have world economic relations, the most significant of which was the EurAsEC (Eurasian Economic Community), which was transformed into the EEU (Eurasian Economic Union). The Eurasian space includes, with its composition, the largest part of the territory of the former USSR, in which the mineral resources presented in the Periodic Table are concentrated. The EAEU brings together countries with the same level of economic development, a common transport and logistics system and common borders. In addition, they are on the “Great Silk Road”, which determines the unity of their economic and political goals, and also aims to create a single digital space.In accordance with the foregoing, the purpose of the study is an analytical assessment of the development model of the digital space of the EAEU for the development of the economy and science.The scientific significance of the study lies in the analysis of the activities of countries united in a single economic union in the era of digitalization and informatization.